Erasure of histone acetylation by Arabidopsis HDA6 mediates large-scale gene silencing in nucleolar dominance - Silva, Manuela (2010)
Nucleolar dominance describes the silencing of one parental set of ribosomal RNA (rRNA) genes in a genetic hybrid, an epigenetic phenomenon that occurs on a scale second only to X-chromosome inactivation in mammals. An RNA interference (RNAi) knockdown screen revealed that the predicted Arabidopsis histone deacetylase, HDA6, is required for rRNA gene silencing in nucleolar dominance. In vivo, derepression of silenced rRNA genes upon knockdown of HDA6 is accompanied by nucleolus organizer region (NOR) decondensation, loss of promoter cytosine methylation, and replacement of histone H3 Lys 9 (H3K9) dimethylation with H3K4 trimethylation, H3K9 acetylation, H3K14 acetylation, and histone H4 tetra-acetylation. Consistent with these in vivo results, purified HDA6 deacetylates lysines modified by histone acetyltransferases whose substrates include H3K14, H4K5, and H4K12. HDA6 localizes, in part, to the nucleolus, supporting a model whereby HDA6 erases histone acetylation as a key step in an epigenetic switch mechanism that silences rRNA genes through concerted histone and DNA modifications